Mindfulness y terapia cognitivo conductual en la regulación emocional de niños con TDAH - Romo Armas, Pamela Judith; Suárez Alcívar, Ana Victoria (My University, 2025)
Attention-Deficit Hyperactivity Disorder (ADHD) affects the emotional self-regulation of many school-aged children. This study aimed to comparatively analyze the effects of Mindfulness and Cognitive Behavioral Therapy (CBT) on emotional regulation in children with ADHD through a systematic review of the scientific literature. The study was conducted using a qualitative paradigm with a systematic review design, applying selection criteria to databases such as Scopus, PubMed, Web of Science, PsycINFO, SciELO, Psicodoc, and Latindex. Studies published between 2015 and 2025 were considered. Twenty studies were selected for the review. The findings showed that both approaches show proven benefits in the management of impulsivity, attention, and emotional control, although with differences in their foundations and methodologies. It was concluded that both CBT and Mindfulness are effective interventions for improving emotional regulation in children with ADHD, and their combined use is therefore recommended.
El Trastorno por Déficit de Atención e Hiperactividad (TDAH) afecta la autorregulación emocional de muchos niños en edad escolar. Este estudio tuvo como objetivo analizar comparativamente los efectos del Mindfulness y la Terapia Cognitivo Conductual (TCC) en la regulación emocional de niños con TDAH a través de una revisión sistemática de literatura científica. Se trabajó bajo el paradigma cualitativo con diseño de revisión sistemática, aplicando criterios de selección en bases como Scopus, PubMed, Web of Science, PsycINFO, SciELO, Psicodoc y Latindex. Se consideraron estudios publicados entre 2015 y 2025. Se seleccionaron 20 estudios para la revisión. Los hallazgos permitieron evidenciar que ambos enfoques muestran beneficios comprobados en el manejo de impulsividad, atención y control emocional, aunque con diferencias en sus fundamentos y metodologías. Se concluyó que tanto la TCC como el Mindfulness son intervenciones eficaces para mejorar la regulación emocional en niños con TDAH por lo que se recomienda promover su uso combinado.
Keywords: ATENCIÓN; HIPERACTIVIDAD; INFANCIA; MINDFULNESS